The relationship between work-life balance and employee retention among employees at Sarawak Broadcasting Department, Kuching, Sarawak / Madeline Angelina Aik - Aik, Madeline Angelina (2019)
This study is to investigate the relationship between work-life balance factors and employee retention among employees. This study was done at Sarawak Broadcasting Department, Kuching, Sarawak. A total of 104 respondents were selected from 7 departments, namely, State Directory, Human Resources Unit, Asset and Store Unit, Section of Current Affair, Account, Marketing and Regulatory Advertising and Public Relations Unit. Data are collected consists of 30 questions related to (flexible work schedule, job burnout, job sharing and employee retention). The questionnaires were distributed to 80 employees of Sarawak Broadcasting Department, Kuching, Sarawak. The type of research design for this study is non-experimental research namely correlational. The sampling technique used is stratified sampling. This study will be conducted by using conceptual framework adopted Azman, Ghani, Hashim, and Sabri (2016). The result indicated that flexible work schedule has negative relationship, significant and moderate correlation. Meanwhile, job burnout has positive relationship and significant correlation. Job sharing resulted no relationship between employee retention.